A Rare Case of Extensive Eggshell Intestinal Wall Peritoneal Calcification in a Long-Term Continuous Peritoneal Dialysis Patient - Erasmia Sampani; Chrysostomos Dimitriadis; Efstratios Kasimatis; Evangelos Memmos; Aikaterini Papagianni (Case Reports in Nephrology)
Encapsulating peritoneal sclerosis (EPS) is a rare but rather serious complication of long-term peritoneal dialysis. The etiology of EPS is multifactorial, with long-term peritoneal dialysis, multiple peritonitis episodes, and uncontrolled hyperparathyroidism considered to be major risk factors for this often life-threatening condition. We report a case of a 55-year-old female patient with Down syndrome and end-stage renal disease (ESRD) on long-term peritoneal dialysis (PD) with extensive intestinal peritoneal calcifications and a rather uncomplicated long follow-up.